Development of the Indonesian Teacher Engagement Index (ITEI) Apps Model without the Internet - ., Sasmoko; Indrianti, Yasinta; Ghadati Rabiha, Sucianna; Anindyo Widhoyoko, Samuel; Rosyidi, Unifah (International Journal of Engineering and Technology, 2018)
The internet network is a resource not always available in some remote areas. It makes them have difficulty in accessing information online. As a result, technological developments in the region are also obstructed. This study attempts to extend the technical approach to improve the utilization of ITEI as a self-diagnostic application that can be accessed offline through a web browser. So teachers who live in remote areas can still learn their profile engagement. With the help of the proposed platform, app developers can easily develop and publish offline Web applications with Web content and simplified external sync capabilities.Â Â